Analysis Of The Relationship Between Personal Protective Equipment (Ppe) Compliance And Workplace Accident Risk: A Literature Review - Nurul Alia Fachrani Kusuma (CV. AFDIFAL MAJU BERKAH, 2026)
Workplace accidents remain a major occupational safety issue across various industries, and low compliance with Personal Protective Equipment (PPE) use continues to increase injury risk. This literature review aimed to analyze the relationship between PPE compliance and workplace accident risk. The study used a qualitative literature review approach by reviewing five quantitative empirical studies published between 2022 and 2025. The findings consistently showed that proper and consistent PPE use was associated with lower workplace accident and injury risk. Knowledge, attitude, and safe work behavior were also identified as important factors influencing PPE compliance. Several studies further showed that incomplete PPE availability, weak supervision, and poor enforcement of safety procedures reduced compliance and increased accident risk. In conclusion, PPE compliance is an important protective factor in improving workplace safety. Therefore, workplace accident prevention should focus not only on PPE provision, but also on strengthening worker education, supervision, and safety culture.